Polydopamine-coated chitosan/calcium pyrophosphate hybrid microflowers as an effective hemostatic agent. (15th November 2019) - Liu, Shangpeng; Zheng, Zhiqin; Wang, Shuang; Chen, Shaojuan; Ma, Jianwei; Liu, Guosai; Wang, Bin; Li, Jiwei
Highlights: Polydopamine-coated chitosan/calcium pyrophosphate microflowers was prepared. The polydopamine coating and porous hierarchical structure promoted the blood clotting. The PDA@CS-CaP hybrid microflowers had no exothermic adverse effects. The PDA@CS-CaP hybrid microflowers showed excellent biocompatibility. Abstract: In this study, polydopamine (PDA) coated chitosan/calcium pyrophosphate hybrid microflowers (PDA@CS-CaP) were prepared using a facile approach and evaluated as a hemostatic agent. The surface morphology and elements, chemical groups, porous structure, thermostability, zeta potential, as well as surface wettability were systematically characterized by scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FTIR), N2 adsorption-desorption, thermogravimetry (TGA) and contact angle apparatus. Due to the synergistic effects of the high hydrophilicity (water contact angel nearly 0), chemical activation (the amino and phenol group of PDA), and the flower-like porous hierarchical structure, the prepared PDA@CS-CaP could induce hemocytes and platelets aggregation, promote the blood clotting and achieve bleeding control in vitro and in vivo. Furthermore, the PDA@CS-CaP had no exothermic adverse effects and exhibited better biocompatibility (no cytotoxicity against fibroblasts cells). Thus, the PDA@CS-CaP were expected to be a promising candidate for a safe and promising hemostatic agent because of its porous and hierarchical structures as well as the active PDA coating.